Digital health and quality of care in Primary Health Care: an evaluation model - Ísis de Siqueira Silva; Cícera Renata Diniz Vieira Silva; Claudia Santos Martiniano; Aguinaldo José de Araújo; Renan Cabral de Figueirêdo; Luís Velez Lapão; Luís Velez Lapão; Renan Cipriano Moioli; Ewerton William Gomes Brito; Severina Alice da Costa Uchôa (Frontiers Media S.A., 2024)
IntroductionThe implementation of technologies in Primary Health Care with monitoring and evaluation of the quality of health care is fundamental to direct the access and quality of health care in the context of the Sustainable Development Goals. Our objective was to develop a model for evaluating digital health interventions in primary care, considering its impact on first contact, longitudinality, integrality and coordination in health.MethodologyThis is an exploratory methodological study of a qualitative nature. This study seeks to explore strategic actors' perceptions of an evaluation model, and was developed in a process between June 2021 and March 2024. The following stages were followed: Identification of previous models available in the literature, model development, model validation, model update. We performed a nominal group consensus technique online with seven experts. Stages taken to define the design of the model: sending the elaborated model, together with an electronic form with 18 subjective questions, such as brainstorming strategy, for recording impressions, judgment of agreement and suggestions; workshop for discussion by videoconference, at the time the objectives and the model diagram were presented, followed by debate with clarification of doubts and suggestions for clarification of the step-by-step design. After incorporating the suggestions, the model agreed upon in the workshop was subjected to another analysis by the same experts, sent in an online Google document, in which possible inconsistencies between the proposed model and the agreed one were verified, as well as the final agreement on the recommended proposal. At the end of this stage, with synchronous and asynchronous remote procedures, consensus was reached.ResultsThe proposed evaluation model presents as primary categories, structure, process and result. The structure encompasses four indicators, namely, employees; financial resources; infrastructure resources; and regulatory and strategic resources. The process is organized into three dimensions, namely: technical dimension, organizational dimension and relational dimension. The results will be evaluated in products; intermediate results; and impacts (short, medium and long term). The results will be measured by the seven pillars of quality: efficacy, effectiveness, efficiency, optimization, acceptability, legitimacy, equity.ConclusionThis study achieved the goal of developing a model to evaluate digital health interventions in Primary Health Care, helping to identify adequate and useful evaluation methods filling the gap of the lack of quality evaluation standards in the brazilian Digital Health Strategy. It presents an important difference in relation to models from different countries, as it considers the impacts on Primary Health Care quality attributes such as first contact care, longitudinality, integrality and coordination of care. The model will be used by managers and health professionals of Primary Health Care in a case study in Brazil to evaluate the quality of health care. It is expected that the proposed model may be used in other evaluation studies and countries through contextual adaptations.